2017
DOI: 10.1055/s-0043-115645
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Clinical Features, and Natural History of Incidental Clinically Non-Functioning Pituitary Adenomas

Abstract: The objective of the study was to assess the prevalence and clinical features of incidentally discovered clinically non-functioning pituitary adenoma (CNFPA) and to analyze its natural history. A multicenter retrospective study in patients diagnosed with incidental CNFPA periodically followed-up in 3 specialized neuroendocrinology units from 1992 to 2015 was performed. Out of a total of 189 CNFPA patients, 57 cases (30.1%; 29 women; age at diagnosis 55.8±16.7 years) were incidental. Most patients (n=55, 96.5%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 26 publications
5
17
2
3
Order By: Relevance
“…Follow-up showed a low rate of recurrence in our NFPA series, in accordance with the majority of reported studies [11,29,30], though not all [31][32][33][34], with or without radiotherapy. A meta-analysis reported a 2-fold higher risk of recurrence without radiotherapy compared to radiotherapy of NFPA [32].…”
Section: Discussionsupporting
confidence: 92%
“…Follow-up showed a low rate of recurrence in our NFPA series, in accordance with the majority of reported studies [11,29,30], though not all [31][32][33][34], with or without radiotherapy. A meta-analysis reported a 2-fold higher risk of recurrence without radiotherapy compared to radiotherapy of NFPA [32].…”
Section: Discussionsupporting
confidence: 92%
“…There is a differential susceptibility to compression among the cell populations of the adenohypophysis, with gonadotropes and thyrotropes being the most susceptible. 12,14,27 In this study, the most common deficits were indeed hypothyroidism and male hypogonadism, affecting almost 50% of included males, similar to prior studies. 4,7,10,13,19,27 The rates of female hypogonadism were consider-ably lower.…”
Section: Endocrine Functionsupporting
confidence: 88%
“…Larger tumor size has long been known to increase the likelihood of hormone dysfunction in a variety of sellar pathologies. [11][12][13]19 In this study, larger tumors were indeed significantly associated with preoperative endocrine dysfunction on bivariate analysis. On multivariable analysis, controlling for patient age and sex, this association was not maintained.…”
Section: Tumor Size and Gland Volumesupporting
confidence: 56%
“…16 A recent study on the natural history of clinically nonfunctioning pituitary incidentalomas reported a tumor growth rate of only 4% in the year following the incidental diagnosis, supporting the practice of noninterventional monitoring of such tumors. 17 Similarly, because of the potential long-term effects of radiation and the strong association of hypopituitarism following pituitary radiation, there has been a call for more conservative management of PA with endocrinological surveillance. 4 With regards to the type of radiation used, there was a decline in the use of EBRTover time, with a simultaneous rise in the rates of use of SRS for PA treatment.…”
Section: Discussionmentioning
confidence: 99%